Increasing Taba Terunjam Village Community Participation in Village Development Meeting Activities - Lorita, Evi; Kader, Bando Amin C.; Ningsih, Marida Sari; Imanda, Antonio; Yusuarsono, Yusuarsono; Handayani, Tuti; Hardand, Hardand (Indonesia Berdaya, 2021)
Village development deliberations are ideally participatory forums that involve all community elements in the planning process. However, in Taba Terunjam Village, community participation remains low, both in terms of attendance and active involvement in expressing aspirations. Through this Community Service Program (PKM), lecturers and students from the Public Administration Study Program at Universitas Dehasen Bengkulu aim to raise awareness and encourage active civic engagement through educational and dialogical approaches. The activity was conducted through socialization and counseling sessions that encouraged residents to take a more active role in village development meetings. The results showed a significant increase in citizen attendance, willingness to voice opinions, and the establishment of more open two-way communication between the community and village officials. This activity proves that with the right strategies, a participatory culture at the village level can be fostered and become a strong foundation for democratic and sustainable development.